The FACTORS AFFECTING THE EFFECTIVENESS OF INTERNAL AUDIT (International Journal of Scientific Research and Management (IJSRM), 2022)
Internal audit (IA) is a vital management technique for ensuring that corporate controls are effective. Additionally, IA is an effective instrument for strengthening governance, increasing operational efficiency, increasing the unit’s worth, and promoting public services. As a result, it is necessary to study and evaluate the elements affecting IA effectiveness, particularly IA independence, prior to establishing and operating IA in order to accomplish IA objectives. The purpose of this essay is to examine the aspects that affect the effectiveness of IA. By analyzing, reviewing, and synthesizing prior research, the article synthesized and proposed factors affecting the effectiveness of internal audit, including IA independence; internal auditor capacity; management support for IA; the quality of IA; the use of information technology in IA; the size of the internal audit department; the relationship between internal and external audit; and the audit committee